Balonkorf: A co-educational and alternative sport in the physical education classroom - García-Pérez, Laura; Salazar-Ruiz, Rosario; Caracuel-Cáliz, Rafael; A. Ramírez-Granizo, Irwin; Sanz-Martín, Daniel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Alternative sports are characterized by being full of motivation, enjoyment and practical involvement. They are used in physical education classes because of their adaptability and ease of adaptation to the students’ abilities, also promoting gender equality. Consequently, the aim of this study was to make a didactic proposal on an alternative sport, "the balonkorf", to work in a playful way on cooperation. It was designed according to the instruction 12/2022 of June 23, for 6th grade of Primary Education with a total of 26 students. The proposal included a seven-session sequence: Session 1 focuses on passing and receiving. Session 2 introduces passing, receiving, and spatial occupation. Session 3 incorporates passing, receiving, spatial occupation, and shooting. Session 4 addresses defensive and offensive tactics. Sessions 5 and 6 integrate passing, receiving, spatial occupation, and tactics. Finally, Session 7 features a formal competition to apply the tactics and techniques developed in previous sessions.